Prioritas Alternatif Keputusan pada Analisis Kredit Motor - Anthony Widiatno; Rudy Aryanto (Bina Nusantara University, 2013)
Non-performing loans are common problem faced by financing companies. One of the companies which is exposed to this problem is a motorcycle dealer. Object of this research is PT. AM, a motorcycle dealer of brand Yamaha. Corporate leaders realized the problem of non-performing credit, and they tried solving the problem by conducting strengthens analysis credit with the purpose to sustain the operational in the future. The methods used in this research were standard credit scoring and method of comparison exponential as decision-making to determine the sequence of alternative counsel by plural criteria. The technique of the data collection was directly face-to-face unstructured interview through. On the stage of standard credit scoring analysis, the data obtained process by giving value. Next on the stage analysis using method of comparison exponential, used the calculation of parameters and eckenrode method. The final results of this research were that good analysis management of credit can reduce the problem of non-performing loans. It is proven of 3 debtor non-performing in notes of the company was 3 debtor equal to the result predictions of this research.